Descriptive Study of Transgender Youth Receiving Health Care in the Gender Identity Program in Southern Brazil - Soll, Bianca Machado Borba; Fontanari, Anna Martha; Brandelli Costa, Angelo; Chinazzo, Ítala; Silva, Dhiordan Cardoso; Guadagnin, Fernanda; Tramontina, Silzá; Lobato, Maria Inês Rodrigues (Frontiers in Psychiatry, 2021)
Since 2014, the Gender Identity Program (PROTIG) of Hospital de Clínicas de Porto Alegre (HCPA) has been assisting transgender youth seeking gender-affirmative treatment offered at a public health-care service specializing in gender in southern Brazil. This article aims to analyze sociodemographic and clinical data regarding the diagnoses of gender dysphoria and gender incongruence, psychiatric comorbidities, and clinical aspects of a sample of transgender youths seeking health care in the gender identity program. The research protocol consisted of a survey of the data collected in the global psychological evaluation performed at the health-care service for youths diagnosed with gender incongruence and their caretakers. Participating in this research were 24 transgender youths between 8 and 16 years old with diagnostic overlap of gender dysphoria [Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5)] and gender incongruence [International Classification of Diseases, 11th Revision (ICD-11)] and 34 of their caregivers. Of the young people, 45.8% were positive for some psychiatric comorbidity throughout their lives, with almost half (45.4%) having two or more psychiatric comorbidities in addition to gender dysphoria. The mental health professionals comprising affirmation care teams face the challenge of adapting the care protocols to the uniqueness of each demand by developing individualized forms to promote healthy development. This can be done by focusing not only on medical and physical interventions for gender affirmation but also on the promotion of mental health and general emotional well-being. Thus, the gender affirmation model, which advocates for global assessment and personalized guidance, proved to be adequate. Nevertheless, access to multidisciplinary health services specializing in gender is essential for promoting the general well-being of the population of transgender youth.